Estrogen receptor 1 expression and methylation of Esr1 promoter in mouse fetal prostate mesenchymal cells induced by gestational exposure to bisphenol A or ethinylestradiol - Bhandari, Ramji K (Environ Epigenet, 2019)
Fetal/neonatal environmental estrogen exposures alter developmental programing of the prostate gland causing onset of diseases later in life. We have previously shown in vitro that exposures to 17β-estradiol (E2) and the endocrine disrupting chemical bisphenol A, at concentrations relevant to human exposure, cause an elevation of estrogen receptor α (Esr1) mRNA in primary cultures of fetal mouse prostate mesenchymal cells; a similar result was observed in the fetal rat urogenital sinus. Effects of these chemicals on prostate mesenchyme in vivo are not well understood. Here we show effects in mice of fetal exposure to the estrogenic drug in mixed oral contraceptives, 17α-ethinylestradiol (EE2), at a concentration of EE2 encountered by human embryos/fetuses whose mothers become pregnant while on EE2-containing oral contraceptives, or bisphenol A at a concentration relevant to exposures observed in human fetuses in vivo. Expression of Esr1 was elevated by bisphenol A or EE2 exposures, which decreased the global expression of DNA methyltransferase 3A (Dnmt3a), while methylation of Esr1 promoter was significantly increased. These results show that exposures to the environmental estrogen bisphenol A and drug EE2 cause transcriptional and epigenetic alterations to expression of estrogen receptors in developing prostate mesenchyme in vivo.